A case study : waste reduction for a metal finishing company - Erten-Munal, Mujde (Knovel, 2011)
A pollution prevention/waste minimization opportunity assessment was conducted for a metal finishing and fabricating facility (Company X). The scope of the business activity of that company included the design, production, assembly, and sale of rubber-coated rollers for office automation equipment; the design, production, and sale of valve stem seals, oil seals and O-rings for automotive engines and components; and the design, production, and sale of custom-molded commercial-grade rubber products.
Keywords: Metals -- Finishing -- Waste disposal -- Case studies.; Metal finishing equipment industry -- Environmental aspects -- Case studies.; elektronické knihy; electronic books